Pengenalan Silpau (Dictyosphaeria Versluysii) bagi Masyarakat Dusun Lemon di Desa Tial Kabupaten Maluku Tengah sebagai Sumber Pangan Alternatif - Sintje Liline; Tri Santi Kurnia (IAIN AMBON, 2022)
The aims of this community service activity are for the community to know the nutritional levels of silpau from the coastal waters of Tial Country and how to use silpau as food from the sea. This community service activity was carried out as counseling to housewives in Lemon Hamlet, Tial Country, Central Maluku Regency. The population in this activity is the entire community of Tial Country with homemakers from Lemon Village as the sample. This community service activity is carried out in the form of counseling. After participating in community service activities, recognize and know about the potential of silpau as a nutritious alternative food ingredient, and how to process it.